Aerial Robots - Aerodynamics, Control and Applications 2017
DOI: 10.5772/intechopen.69396
|View full text |Cite
|
Sign up to set email alerts
|

Computational Aeroelasticity of Flying Robots with Flexible Wings

Abstract: A computational co-simulation framework for flying robots with flexible wings is presented. The authors combine a nonlinear aerodynamic model based on an extended version of the unsteady vortex-lattice method with a nonlinear structural model based on a segregated formulation of Lagrange's equations obtained with the Floating Frame of Reference formalism. The structural model construction allows for hybrid combinations of different models typically used with multibody systems such as models based on rigid-body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Konstadinopoulos et al, 1981; Preidikman et al, 2017; Roccia et al, 2013; Verstraete et al, 2015). On the other hand, the numerical procedure adopted for Simulator 1 to solve the EoMs of the harvester array is based on Hamming’s fourth-order predictor–corrector method (Carnahan et al, 1969; Preidikman et al, 2017). This method requires that the set of second-order differential equations presented in equation (4) to be re-written as a first-order system of ODEs.…”
Section: Simulation Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Konstadinopoulos et al, 1981; Preidikman et al, 2017; Roccia et al, 2013; Verstraete et al, 2015). On the other hand, the numerical procedure adopted for Simulator 1 to solve the EoMs of the harvester array is based on Hamming’s fourth-order predictor–corrector method (Carnahan et al, 1969; Preidikman et al, 2017). This method requires that the set of second-order differential equations presented in equation (4) to be re-written as a first-order system of ODEs.…”
Section: Simulation Schemementioning
confidence: 99%
“…This feedback between the aerodynamics and the movement of the harvesters (flow field boundaries) generates a strong coupling between the flow and structural models. In order to capture these complex interactions with a numerical model, in this work, the authors have chosen a two-way non-monolithic coupling method strategy (Preidikman et al, 2017;Roccia et al, 2017). Erturk et al (2010) represented the physical system shown in Figure 1 using a lumped-parameter model in which the harvester is idealized as a 2D airfoil (see Figure 2).…”
Section: Piezoelastic Modelmentioning
confidence: 99%
“…47 Their proposed three-dimensional (3D) fluid-structure interaction of the flapping locomotion is coupled with a preconditioned Navier-Stokes solution with a non-linear co-rotational structural solution. Preidikman et al 48 combined a nonlinear aerodynamic model based on an extended version of the unsteady vortex-lattice method with a nonlinear structural FE model based on a segregated formulation of Lagrange's equations. Lee et al 49 studied the wing flexibility effects on the flight performance of FAV.…”
Section: Introductionmentioning
confidence: 99%